THE INFLUENCE OF JOB INSECURITY AND JOB STRESS ON ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION IN EMPLOYEES IN STARTUP COMPANIES IN MEDAN CITY - Fani Agustriani; Prihatin Lumbanraja; R. Hamdani Harahap (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Organizational commitment is an important aspect that determines the long-term performance and success of a company. Business developments continue to change so it is necessary to look at employee security in maintaining their jobs. Job insecurity and job stress are important issues in the dynamic and unstable startup work environment, which can have a negative impact on employees' well-being, job satisfaction and organizational commitment. Job satisfaction felt by employees can also reduce job satisfaction which has an impact on increasing performance. Employees who are satisfied with the work they have obtained will be motivated to improve their performance so that it will have an impact on increasing overall organizational performance thereby increasing loyalty and productivity in their company. The aim of this research is to analyze the influence of job insecurity and work stress on organizational commitment through job satisfaction in employees of startup companies in the city of Medan. The population in this study was 420 employees from 47 Startup companies in Medan City from various businesses so that the population was used as a sample of 100 respondents. Data were analyzed using descriptive analysis and SEM (Structural Equation Model) analysis. with the sampling method used Simple Random Sampling or Proportional Stratified Random Sampling. The research results show that job insecurity directly has a negative and significant effect on job satisfaction and is significant on organizational commitment, work stress has a negative and significant effect on job satisfaction and is significant on organizational commitment, and job satisfaction has a positive and significant effect on organizational commitment. Indirectly, job insecurity has a negative and significant effect on organizational commitment through job satisfaction and job stress has a negative and insignificant effect on organizational commitment through job satisfaction.